The interrelation between major depressive symptoms and ambivalence over emotional expression among college students: a network perspective on gender differences - Chen, Xiangxiang (Frontiers in Psychiatry, 2025)
IntroductionMajor depressive disorder is a common and severe mental disorder among college students. Meanwhile, depressive symptoms and ambivalence over emotional expression are closely related, while little research explores their bidirectional relationship. To address this gap, the current study employed a network approach to identify the interrelation between depressive symptoms and ambivalence over emotional expression among college students.MethodsInitially, 2,103 college students were recruited and completed the patient health questionnaire (PHQ) -9 and the ambivalence over emotional expression questionnaire (AEQ). In the final analysis, 1,362 college students passed the attention check and were included (674 females; age: Mean = 18.61, SD = 0.84). The symptom network approach was employed to explore the interrelation between depressive symptoms and ambivalence over emotional expression, as well as to explore the gender difference between symptom networks.ResultsThe strongest edges between depression and ambivalence over emotional expression were observed between “concentration difficulties” (PHQ7) and “emotional rumination” (AEQ1), as well as between “guilt” (PHQ6) and “regret expressing” (AEQ5) in the overall sample. The edge between “inhibit positive emotion expression” (AEQ3) and “inhibit negative emotion expression” (AEQ4) was the strongest edge weight in male and female networks. For bridging symptoms, “concentration difficulties” (PHQ7), “emotional rumination” (AEQ1), “guilt” (PHQ6), and “regret expressing” (AEQ5) were the biggest bridging symptoms (Z score above 1) that linked depression symptoms and ambivalence over emotional expression. Between gender networks, “guilt” (PHQ6) was the common and strongest bridging symptom (Z score above 1) in both male and female networks. Network robustness and stability were also estimated.ConclusionThe current study provides a new perspective on the interrelation between depressive symptoms and ambivalence over emotional expression, as well as examines the gender difference. In light of the findings, further intervention, such as cognitive control training or mindfulness-based interventions that focus on bridging symptoms, may disassociate the interrelation between depression and ambivalence over emotional expression.